1989
DOI: 10.1007/bf01311120
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of nuclear lamina protein in human fibroblasts infected with cytomegalovirus (HCMV)

Abstract: Immunoblotting with monoclonal as well as polyclonal lamin antibodies revealed that nuclear lamina proteins of human foreskin fibroblasts (HFF) were differentially affected after infection with human cytomegalovirus (HCMV). Lamin A immunoreactivity was progressively lost during the course of the infectious cycle whereas that of lamin C was comparatively stable. This process was not observed in herpes simplex virus-infected HFF. On the other hand, noninfected arrested HFF stimulated by serum to enter S-phase al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…These data corroborate the studies of Radsak and colleagues demonstrating that HSV-1 infection does not induce altered electrophoretic mobilities of lamins in human fibroblast cells infected with wild-type HSV-1 (22,23).…”
Section: Downloaded Fromsupporting
confidence: 90%
“…These data corroborate the studies of Radsak and colleagues demonstrating that HSV-1 infection does not induce altered electrophoretic mobilities of lamins in human fibroblast cells infected with wild-type HSV-1 (22,23).…”
Section: Downloaded Fromsupporting
confidence: 90%
“…1E, top panels). The loss of immunoreactivity of lamin A (which is not caused by proteolysis) is a late event during the course of HCMV replication as described previously by Radsak et al (24). In our analysis, a general alteration in the amount of cellular protein in virus-infected cells could be excluded by the control staining of constant levels of ␤-actin Fig.…”
Section: Pul97 Induces Alterations In the Subnuclear Localization Patsupporting
confidence: 79%
“…Structural destabilization of the nuclear lamina is generally mediated through phosphorylation of nuclear lamins (2). In HCMV-infected cells, alterations of the nuclear lamina were described (24,44); however, the identity of protein kinases involved in lamin phosphorylation has remained speculative so far. Our data provide evidence for the recruitment of a virus-encoded protein kinase to the nuclear lamina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main components of the nuclear lamina are the lamins, which, based on their expression patterns, properties and location, can be divided into two main classes: A-type lamins, including lamin A, AD10, C and C2; and B-type lamins, including lamin B1, B2 and B3 (Broers et al, 1997(Broers et al, , 2006Rzepecki, 2002;Stuurman et al, 1998). Several studies have shown that herpesvirus infection causes structural and biochemical rearrangements of nuclear lamina components, to ensure the efficient production of viral progeny (Leach et al, 2007;Marschall et al, 2005;Morris et al, 2007;Mou et al, 2007;Muranyi et al, 2002;Radsak et al, 1989;Reynolds et al, 2004;Scott & O'Hare, 2001). Notably, murine cytomegalovirus (MCMV) and, more recently, herpes simplex virus type 1 (HSV-1) have been reported to recruit cellular protein kinases C (PKCs) at the nuclear rim, and, as a consequence, induce an increase in phosphorylation of nuclear envelope proteins, including lamins and emerin, to promote nuclear lamina dissolution (Leach et al, 2007;Morris et al, 2007;Muranyi et al, 2002;Park & Baines, 2006).…”
Section: Introductionmentioning
confidence: 99%